2007
DOI: 10.1080/08860220701460178
|View full text |Cite
|
Sign up to set email alerts
|

Acute Renal Failure Associated with Rhabdomyolysis in Acute Q Fever

Abstract: The clinical presentation of Q fever is polymorphic and non-specific, and it may be presented as an acute or chronic disease. Renal complications of acute Q fever such as acute glomerulonephritis are not uncommon. Acute renal failure induced by rhabdomyolysis in acute Q fever has until now never been reported in the literature. We presented a case of acute Q fever associated by extreme rhabdomyolysis and consecutive acute renal failure. A male patient was treated with doxycycline and continuous venovenous hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Three samples from patients infected with Hepatitis B virus with kidney dialysis of whom 1(33%) IgM and IgG positive. These patients listed below immunocom promised patients, this result supported with Ljutic D, et al [17] who suggested that Acute Q fever should be thought of as a potential reason of acute kidney failure Vizinho R, et al [18] mentioned that chronic Q fever has antecedently solely delineated in two dialysis patients Gwida M, et al [19] mentioned that there is a requirement for further analysis on the impact of Q fever on each veterinary and public health [20][21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 72%
“…Three samples from patients infected with Hepatitis B virus with kidney dialysis of whom 1(33%) IgM and IgG positive. These patients listed below immunocom promised patients, this result supported with Ljutic D, et al [17] who suggested that Acute Q fever should be thought of as a potential reason of acute kidney failure Vizinho R, et al [18] mentioned that chronic Q fever has antecedently solely delineated in two dialysis patients Gwida M, et al [19] mentioned that there is a requirement for further analysis on the impact of Q fever on each veterinary and public health [20][21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 72%
“…Sometimes renal failure in Q fever may not to be related with acute glomerulonephritis or TIN as in our case. A case of acute Q fever associated by extreme rhabdomyolysis and consecutive acute renal failure treated with continuous venovenous hemodiafiltration was presented [13]. …”
Section: Discussionmentioning
confidence: 99%